EFFECT OF COLLABORATION APPROACHES ON EMPLOYEE EFFICIENCY AND JOB-RELATED OUTCOMES: TRANSFORMED BUSINESS MODEL APPROACH IN TRAINING AND DEVELOPMENT - Gosula, Emmanuel (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Purpose: The purpose of this study is to determine whether employee productivity in information technology (IT) companies can be sustainedly improved by the organizational collaboration strategy. Additionally, in order to offer insights for improving workplace dynamics and employee performance in the IT industry, it aims to investigate how employee efficiency effects important job-related outcomes, such as job satisfaction, organizational commitment, and team spirit. Methodology: A correlational research design was employed for this study, utilizing a quantitative approach to examine the relationships between the organizational collaboration approach, employee efficiency, and job-related outcomes in the Indian IT sector. Data was collected through a survey distributed using convenience sampling to employees in various IT organizations across India. A 5-point Likert scale was used to measure key variables, including organizational collaboration, employee efficiency, job satisfaction, organizational commitment, and team spirit. Structural equation modelling (SEM) was conducted using SPSS and AMOS to analyze the direct and indirect relationships among variables, with reliability and validity checks performed through Cronbach’s alpha and Average Variance Extracted (AVE). Findings: According to the study, employee productivity in the Indian IT sector is significantly and sustainably impacted by the organizational collaboration method. The impact of employee efficiency on job satisfaction, organizational commitment, and team spirit was also found to be significant. Strong favourable correlations between employee performance outcomes and cooperation practices were found using structural equation modelling (SEM) analysis. According to the findings, workers who feel that their workplace is collaborative are more productive, which raises job satisfaction and organizational commitment levels, which in turn fosters a sense of camaraderie and harmony among coworkers. Implication: Academically, this study adds a quantitative evaluation of how collaboration affects important job-related outcomes to the expanding corpus of information on organizational cooperation and employee efficiency, particularly in the IT sector. The results of this study have practical implications for IT businesses. Specifically, they indicate that investments in collaborative work environments can increase employee efficiency and, consequently, job satisfaction, organizational commitment, and team spirit—all of which are critical for long-term success. From a social perspective, the study emphasizes how collaborative techniques can enhance workplace culture and employee well-being. This can result in more cohesive, motivated, and inclusive teams that benefit people as well as the larger community.